Sport, the Remedy of Stress - Keczeli, Danica (International Journal of Engineering and Management Sciences, 2019)
The study examines the relationship between mental health, resilience and perceived stress among leisureand competitive athletes. Three questionnaires (Keyes Mental Health Continuous Scale, Detected Stress Questionnaire, and 10-item CD-RISC Questionnaire) were studied, filled out by a total of 436 people, of which 297 were competitive athletes and 139 leisure athletes. The main question of my research was whether there is a difference between these three variables, and how resilience and perceived stress affect three factors of mental health, athletes in leisure and competition. The results show that for all variables the athletes of the competition achieved a better average value than the leisure athletes, and I could show a significant difference in the mean values in the case of the emotional and social well-being variables. Moreover, perceived stress had a greater impact on emotional well-being, while resilience had a positive effect on psychological and social well-being.